Acylation of nitrobenzene and substituted nitrobenzenes by benzoyl chloride using GaClx- and GaAlClx-grafted meporous Si-MCM-41 catalysts - Choudhary, Vasant R.; Jha, Rani (Microporous and Mesoporous Materials, 2009)
A acylation of nitrobenzene and substituted nitrobenzene by benzoyl chloride can be accomplished with good yield in a short reaction period (<= 3 h), even in the presence of moisture, using GaClx- and GaAlClx-grafted mesoporous silica (Si-MCM-41) catalyst. The catalyst is reusable/environmentally friendly. The presence of moisture in the catalyst has beneficial effect on the acylation reaction. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: Acylation; Benzoyl chloride; GaAlClx-grafted Si-MCM-41; GaClx-grafted Si-MCM-41; nitrobenzene

Dopant induced effect on electrocatalytic reduction of nitrobenzene using conducting polypyrrole thin film electrodes - Adhikari, Arindam; Radhakrishnan, S. (Journal of Applied Polymer Science, 2011)
Conducting polypyrrole electrodes were prepared by electrochemical polymerization of pyrrole on vacuum-metallized glass substrates. These electrodes were modified by doping with a range of metal halides as dopant ions having different electronegativity. Electrochemical reduction of nitrobenzene using these electrodes was studied by means of cyclic voltammetry technique in acetonitrile medium containing aqueous HClO(4) (0.1M) as supporting electrolyte. It was found that the electronegativity of the dopant ion played a very important role in the electrocatalytic activity. Polypyrrole doped with nickel chloride gave the highest anodic current at the reduction potential of nitrobenzene. The results were explained on the basis of charge transfer efficiency at the electrode-electrolyte interface, which was associated with the acceptor state created by the dopant in the semi-conducting polymer. (C) 2010 Wiley Periodicals, Inc. J Appl Polym Sci 120: 719-724, 2011
Keywords: charge transfer; conducting polymer; Doping; electrocatalysis; nitrobenzene; polypyrrole; reduction

A detailed study on heat of reaction and heat rate determination of nitrobenzene hydrogenation to aniline reaction using power compensation reaction calorimeter - Kumar, Rajendra; Mane, Pradip R.; Shingote, Savita K.; Mali, Nilesh A. (Process Safety Progress, 2025)
The present study reports experimental heat of reaction and heat rate data of nitrobenzene hydrogenation to aniline reaction with process parameter variation. A high-pressure isothermal power compensation reaction calorimeter was used for this work. A systematic and step-by-step procedure is also reported to determine the heat of reaction and heat rate for a highly exothermic reaction. The sensitivity of experimental molar heat of reaction (kJ/mol) and evolved heat rate (W) values for nitrobenzene hydrogenation reaction was analyzed for various important process parameters, such as temperature, pressure, substrate quantity, solvent quantity, catalyst quantity, RPM, and hydrogen feed rate. Nitrobenzene hydrogenation reactions were conducted using ethanol as solvent and 5% Pd/C as a catalyst with 55-65 degrees C temperature and 7-9 Bar absolute pressure range. More than 99.99% conversion of nitrobenzene to aniline was obtained, and no other by-products were found. The average experimental nitrobenzene hydrogenation heat of reaction of 21 different experiments was found to be -581.87 kJ/mol, and the maximum heat rate during the nitrobenzene hydrogenation reaction was found to be 16.16 W for experiments using 10 gm of nitrobenzene in solvent.
Keywords: heat of reaction; heat rate; Hydrogenation; nitrobenzene; power compensation; reaction calorimeter

Liquid phase nitration of benzene to nitrobenzene using a mesoporous MoO3/Nb2O5 nanocatalyst - Kalbande, Pavan Narayan; Swapna, Bhattu; Sudarsanam, Putla; Umbarkar, Shubhangi B. (Catalysis Letters, 2025)
This work reports the synthesis of a mesoporous MoO3/Nb2O5 catalyst by a facile co-precipitation method for the liquid phase nitration of benzene to nitrobenzene, which is a vital industrial reaction. Pristine Nb2O5 and MoO3/Nb2O5 nanocatalysts were characterized using various techniques, including powder XRD, N-2 adsorption-desorption, Raman, SEM/TEM, pyridine FT-IR, and XPS. The MoO3/Nb2O5 catalyst (10 wt% MoO3 with respect to Nb2O5) showed uniform dispersion of Mo and Nb species, higher amount of oxygen vacancies, and more Br & oslash;nsted acid sites, resulting in a 90% yield of nitrobenzene. In contrast, only 35 and 58% yields were obtained in the case of commercial Nb2O5 and nanosized Nb2O5, respectively. The liquid phase nitration of benzene was carried out using commercial 65% HNO3 as a nitrating agent without sulfuric acid. The mesoporous MoO3/Nb2O5 catalyst is structurally stable, as confirmed by the characterization of the spent catalyst. However, a gradual decrease in the yield of nitrobenzene was observed, which could be due to the leaching of MoO3 species from the catalyst surface.
Keywords: Benzene nitration; Bronsted acid sites; Mesoporous MoO3/Nb2O5 Catalyst; nitrobenzene; Uniform metal dispersion

Ultra-small Pd nanoparticles on SBA-15: an efficient catalyst for one-pot reductive alkylation of nitrobenzene with size-dependent activity - Soni, Yogita; Philip, Milda C.; Vinod, Chathakudath P. (Topics in Catalysis, 2025)
One-pot reductive alkylation of nitrobenzene with alcohol is an important organic synthesis reaction to form 2 degrees amines. In the present work, we have demonstrated that Pd/SBA-15 can be an effective catalytic system for this reaction. We have designed ultra-small Pd nanoparticles supported on SBA-15 for the synthesis of secondary amine, N-ethylaniline, through one-pot reductive alkylation of nitrobenzene with ethanol under ambient conditions. Ethanol functions both as the alkylating agent and the solvent in this process. The reaction is driven by the simultaneous hydrogenation of nitrobenzene to aniline, dehydrogenation of ethanol to aldehyde, and condensation of aniline and acetaldehyde to form N-ethylaniline. The size of the Pd nanoparticles plays a decisive role in the product selectivity. The undercoordinated sites present on ultra-small Pd NPs can facilitate ethanol dehydrogenation to acetaldehyde, thereby enhancing the selectivity towards N-ethylaniline compared to larger Pd nanoparticles. We have also studied the effect of different mesoporous supports such as SBA-15, MCM-41, and KIT-6 on the N-ethylaniline selectivity and found that SBA-15 was most selective. We have demonstrated that by carefully designing the catalyst such as controlling the Pd NPs size to obtain the maximum quantity of undercoordinated sites and choosing suitable support, the aliphatic alcohols can also be used for reductive alkylation of nitrobenzene in one-pot with optimum yields of N-alkylaniline.
Keywords: KIT-6; MCM-41; Modified deposition precipitation; nitrobenzene; Pd nanoparticles; Reductive alkylation; SBA-15; secondary amines; Undercoordinated Pd sites